TRAINING DAN ASISTENSI SISTEM KEUANGAN DESA (SISKEUDES) di DESA KARYA MAKMUR SUNGAILIAT KABUPATEN BANGKA - Rulyanti Susi Wardhani; Suhdi Suhdi; Anggraeni Yunita; Maya Yusnita (Jurnal Abdi Insani, 2022)
Activities in managing village finances which are village rights and obligations that are valued in terms of money and goods, can be included in the category of village financial management, which contains planning, implementation, administration, reporting, and accountability of village finances; this is adjusted to Permendagri No.20 of 2018. The submitted report was still reporting responsibility in the village of Karya Makmur, which still made mistakes. The Bangka Belitung University Service Team conducted training and assistance for siskeudes in Karya Makmur Village. The purpose of this activity is to carry out training and mentoring of the village financial system, which is an application that can be used to help the village government manage village finances from the planning stage to the reporting and accountability stages correctly and appropriately. The activity method carried out by the service team is by approaching the village apparatus for training and assistance from the Siskeudes system. The parties involved in this activity were the study team and the Bangka Belitung Financial and Development Supervisory Agency (BPKP). The results of the activities of the apparatus have explained the errors that often occur from filling out the Siskeudes so that the Karya Makmur Village apparatus can avoid mistakes and have carried out a team evaluation related to financial recording with Siskeudes which has been carried out properly by starting with planning to implementing activities and making accountability reports. The existence of training and assistance on the village financial system in Makmur Sungailiat Village, Bangka Regency, increased the capacity of the village apparatus in managing village finances so that the management and administration of village finances, starting from planning, implementation, administration, reporting, and accountability were more orderly, transparent and accountable.